علاقة مكة بالقبائل والحواضر العربیة قبل الاسلام (Journal of the College of Education for Women, 2019)
The Jarajima were drive away from Mecca at the beginning of third century A.DKhuza"a was settled in Mecca with the help of kinana . Mecca had a lot of relationswith other Arab tribes by trade and marriage . Quais Ailan tried to role Mecca butshe disappointed .Khuza"a tried to extend outside of Mecca but she failed . then this tribemanaged to increase security and stability in Mecca . That encouraged themerchants to come to Mecca.At the beginning of fifth century A.D. Quraish began to get rid of Khuza"a inorder to have the mastery of Mecca. In spite of that Khuza"a remained in herhouses and wrote many peace treaties and intermarriage with Quraish .Quraish managed to control at Mecca in the middle of the fifth century. The sonsof Qusai differed about the role of Mecca. Later on they agreed that Hijba , theLewa" and the dar of Nadwa for the sons of Abid AL Dar while the Siqaya andRifada for the sons of Abid Munaf .Quraish achieved the security and public order , to settle the trade and it'sorganization. Add to that Quraish Found a lot of organizations and wrote manypeace treaties with the Arab tribes .Quraish found the system of Hums ,Fudhul alliance and the Elaf . These are thesocial and economic organizations that complete each others.The mention of Elaf in Quran is very good prove for the importance of the Arabtrade in pre-Islamic time .The Romains and Persians recognized that ,so they gavethe Arab security and preserve. The Arab managed to prepare the security forMecca , Arab tribes and for central civilizations.